Austeridad y defensa: los discursos de las élites económicas centroamericanas durante la pandemia - Robles-Rivera, Francisco; Alvarenga, Ximena; Fuchs, Gustavo (El Colegio de México, 2023)
Central American economic elites have been reluctant to implement redistributive and democratic policies even during crises. This article analyzes the discourse of the economic elites during the first six months of the Covid-19 pandemic in Central America. It analyzes the discourse in the public declarations on economic and fiscal matters issued by the business chambers of each country in response to the emergency. It argues that the discourse of the Central American elites can be divided into two categories: a) discourse that prioritized an agenda of austerity and to a lesser extent, reflected tensions with the government and b) discourse that called for the defense of the business chambers, reflecting more discursive tensions with the government.